Inter-organisational Design of Voluntary Sustainability Initiatives Increasing the Legitimacy of Sustainability Strategies for Supply Chains - Peters, Nils.; SpringerLink (Online service) (Wiesbaden : Gabler, 2010)
Voluntary sustainability initiatives (VSIs) have become the most applied approach for companies to set environmental or social obligations for their supply-chains. However, companies face two main challenges in the design of VSIs: Firstly, they recognise acceptance problems by different stakeholders and opposition by competing initiatives. Secondly, they experience significant resource demands to set up VSIs and ask for more efficient solutions. Nils Peters addresses these challenges by empirically analysing the key resources and complementarities that enable companies to efficiently establish effective designs of VSIs both in terms of participants$1 (Bcompliance and the acceptance of initiative-external stakeholders.s
Conceptual aspects of voluntary sustainability initiatives in the context of proactive sustainability strategies for supply chains -- Theoretical aspects of designing voluntary sustainability initiatives for supply chains -- Initial framework: a resource-based view of institutional entrepreneurship in the design of voluntary sustainability initiatives for supply chains -- An exploratory study of the institutional entrepreneur's resources in the design of legitimised voluntary sustainability initiatives for supply chains -- Development of the research model: resources, the design of voluntary sustainability initiatives for supply chains, and legitimacy -- A confirmatory study of the institutional entrepreneur's resources in the design of legitimised voluntary sustainability initiatives for supply chains -- Conclusion, further research and implications for business practice.
Keywords: Economics; Industrial management; Economics/Management Science; Management/Business for Professionals